The use of migration data to define functional regions: The case of the Czech Republic. (November 2016) - Halás, Marián; Klapka, Pavel; Tonev, Petr
Abstract: The paper analyses migration flows with the purpose of defining functional regions at a micro level. It proposes an innovative approach to the processing of migration data. It includes a reflection on local level migration analysis in relation to local labour markets, and it is inspired by time geographical concepts and research into human spatial behaviour. Relevant identified migration flows are those that occur when a migrant only changes the place of permanent residence, and does not necessarily need to change workplace or most of the localities within a daily timespace context. The paper uses these migration data to delineate local migration areas (daily spatial systems) of the Czech Republic through the application of a standard rule-based procedure of functional regional taxonomy. Highlights: Identifying relevant intrastate migration data at a micro regional level by analysis of spatial behaviour of individuals. Use of the relevant portion of the migration data in order to define local migration areas. Validation of the applicability of migration data to the definition of functional regions at a micro regional level. Use of the territory of the Czech Republic as the example for the proposed approach.